FORMING AN ANALYTICAL MODEL FOR POSITIONING A COMPANY’S BRAND - KOSTENYUK, Yulia; BEZPIATKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the application of brand mapping as an effective analytical tool for evaluating the strategic positioning of educational institutions within the foreign language learning services market. It outlines the methodological foundations of brand mapping and substantiates the suitability of using the “price–quality” axes to assess the competitive potential of educational enterprises. Particular attention is given to the analysis of the Flash English language school, whose position in the market is examined relative to its key competitors, including Green Forest, AntiSchool, Speak Up, English Prime, and the London School of English. The study reveals that the Flash brand occupies an intermediate yet strategically advantageous niche characterized by a balanced combination of moderate pricing and high-quality instruction. This positioning strengthens the brand’s flexibility in competitive interaction, enhances its adaptability to diverse consumer needs, and increases its attractiveness to different segments of learners. The research identifies several core competitive advantages of Flash: an original teaching methodology, a team of highly qualified instructors, adaptable and learner-centered educational programs, and the availability of an integrated online platform that effectively combines traditional and distance learning formats. A comprehensive comparative analysis of competitors demonstrates a high degree of market segmentation, emphasizing the importance of strategies that reconcile affordability with educational quality. The findings confirm that constructing a brand map based on price–quality criteria provides a systematic framework for assessing the competitive environment, determining brand strengths and weaknesses, and substantiating the optimal market positioning of an educational enterprise.